2015
DOI: 10.1007/s00213-015-4086-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinically effective OCD treatment prevents 5-HT1B receptor-induced repetitive behavior and striatal activation

Abstract: We report novel 5-HT1BR-induced behaviors and striatal activation that were alleviated only by clinically effective pharmacological OCD treatment. Studying the mechanisms underlying these effects could provide insight into OCD pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 37 publications
(51 reference statements)
4
41
0
Order By: Relevance
“…While some have suggested that the female Fmr1 KOs should be included in studies with males based on similarity, here we highlight the marked phenotypic differences, and as such, future research could focus on how these phenotypes could, and should, be treated separately. For instance, repetitive behavior phenotypes are commonly treated using several different types of drugs, including 5‐HT1BR agonists (Ho et al., 2016), 5HT1A partial antagonists (Chugani et al., 2016) and more recently, antioxidants (Hardan et al., 2012). Through the routine exclusion of females from biomedical studies, opportunities are missed to explore potential treatments and how sex may impact the efficacy of such treatments.…”
Section: Discussionmentioning
confidence: 99%
“…While some have suggested that the female Fmr1 KOs should be included in studies with males based on similarity, here we highlight the marked phenotypic differences, and as such, future research could focus on how these phenotypes could, and should, be treated separately. For instance, repetitive behavior phenotypes are commonly treated using several different types of drugs, including 5‐HT1BR agonists (Ho et al., 2016), 5HT1A partial antagonists (Chugani et al., 2016) and more recently, antioxidants (Hardan et al., 2012). Through the routine exclusion of females from biomedical studies, opportunities are missed to explore potential treatments and how sex may impact the efficacy of such treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort 3 consisted of 6 KO and 6 WT male mice (2–4 months), and were used for biochemical studies of the PSD. Sample sizes were selected based on estimates from our previous work 36 38 .…”
Section: Methodsmentioning
confidence: 99%
“…5HT 1A agonists reduce stereotypy (Korff et al, 2008; Tucci et al, 2013, 2014b), while 5-HT 1A receptor activation promotes adenylyl cyclase sensitization (Hensler et al, 1996), supporting a role for 5HT 1A/B G i dependent adenylate cyclase-cAMP coupling in OCD (Marazziti et al, 2001; Perez et al, 2001) and its response to treatment. Indeed, clinically effective OCD treatments prevent 5-HT 1B receptor-induced repetitive behavior and striatal activation (Ho et al, 2015). Furthermore, elevated cAMP in H mice could be related to increased 5HT 1A -adenylate cyclase-cAMP signaling with reduced hydrolysis by PDE4 (Korff et al, 2009).…”
Section: Insights Into Ocd From the Deer Mouse: A Platform For Resmentioning
confidence: 99%